2012
DOI: 10.1007/s10657-012-9299-2
|View full text |Cite
|
Sign up to set email alerts
|

Dixit versus Williamson: the ‘fundamental transformation’ reconsidered

Abstract: Comparing the literature on hold-up and strategic entry deterrence leads to a puzzling role for sunk or specific investments in affecting investor’s incentive. In one case, non-redeployable investments decrease investor’s ex-post bargaining power. In the other they increase it. When the entry deterrence effect is acknowl- edged, the threat of hold-up against investor is largely weakened. Contrary to pre- vious literature, in this respect, asset specificity may even constitute an endogenous enforcement device f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The researcher argued that the purchasing policy depends on the practices of the organization. In contrast, the proposed model by Nicita & Vatiero (2014) showed that the transactional cost depends on the nature of the organization in terms of whether it is private or public. Private organizations are seen to be good in internal development while public organizations mainly outsource products.…”
Section: Transaction Cost Economics Theorymentioning
confidence: 92%
See 2 more Smart Citations
“…The researcher argued that the purchasing policy depends on the practices of the organization. In contrast, the proposed model by Nicita & Vatiero (2014) showed that the transactional cost depends on the nature of the organization in terms of whether it is private or public. Private organizations are seen to be good in internal development while public organizations mainly outsource products.…”
Section: Transaction Cost Economics Theorymentioning
confidence: 92%
“…The researcher notes that an organization"s decisions on whether to produce internally or outsource their production are influenced by how controlling their government is or is not. Figure 12 showed that Nicita & Vatiero (2014) have also proposed their own model to study the factors affecting TCE theory. These include administrative regulations, the nature of the organization, market safeguards, and the nature of commodities.…”
Section: Transaction Cost Economics Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, how to reduce the costs of future disturbances in the relations between the firm and its contractual partners is emphasized. Safeguards that align incentives, are often devised by the contractual parties themselves (Williamson 1988(Williamson , 2002Nicita and Vatiero 2014). In accordance with transaction cost economics, we discuss how corporate law can help the firm with contractual solutions that reduce future contractual problems.…”
Section: Nexus For Contractsmentioning
confidence: 98%
“…Although Williamson stressed that transaction frequency should be considered as a vital organisational determinant, numerous researchers tend to overlook this dimension whilst conducting entry mode studies [see e.g. Dietrich 1994;Bremen et al 2010;Nicita & Vatiero 2011].…”
Section: Transaction Costs As the Entry Mode Determinantsmentioning
confidence: 99%